Steroid use and long-term health risks in former athletes - Parssinen, M.; Seppala, T. (Sports Medicine, 2002)
This article focuses on anabolic steroid adverse effects on the cardiovascular system and mental health issues as well as the possible increase in the incidence of neoplasms in anabolic steroid users. On the basis of findings in the literature, the authors consider these three issues as the most significant concerning morbidity and mortality among anabolic steroid users. A study by Parssinen et al. (2000) has shown an increased incidence of premature mortality among power lifters. Anabolic steroids and other concomitantly used drugs are the probable cause of this increased mortality, as power training itself does not increase health risks and all types of physical activity promote health.